Expression of inhibitory receptors on intratumoral T cells modulates the activity of a T cell-bispecific antibody targeting folate receptor. (1st February 2016) - Schreiner, Jens; Thommen, Daniela S.; Herzig, Petra; Bacac, Marina; Klein, Christian; Roller, Andreas; Belousov, Anton; Levitsky, Victor; Savic, Spasenija; Moersig, Wolfgang; Uhlenbrock, Franziska; Heinzelmann-Schwarz, Viola A.; et al.
ABSTRACT: T-cell bispecific antibodies (TCBs) are a novel therapeutic tool designed to selectively recruit T-cells to tumor cells and simultaneously activate them. However, it is currently unknown whether the dysfunctional state of T-cells, embedded into the tumor microenvironment, imprints on the therapeutic activity of TCBs. We performed a comprehensive analysis of activation and effector functions of tumor-infiltrating T-cells (TILs) in different tumor types, upon stimulation by a TCB targeting folate receptor 1 and CD3 (FolR1-TCB). We observed a considerable heterogeneity in T-cell activation, cytokine production and tumor cell killing upon exposure to FolR1-TCB among different FolR1-expressing tumors. Of note, tumors presenting with a high frequency of PD-1 hi TILs displayed significantly impaired tumor cell killing and T-cell function. Further characterization of additional T-cell inhibitory receptors revealed that PD-1 hi TILs defined a T-cell subset with particularly high levels of multiple inhibitory receptors compared with PD-1 int and PD-1 neg T-cells. PD-1 blockade could restore cytokine secretion but not cytotoxicity of TILs in a subset of patients with scarce PD-1 hi expressing cells; in contrast, patients with abundance of PD-1 hi expressing T-cells did not benefit from PD-1 blockade. Our data highlight that FolR1-TCB is a promising novel immunotherapeutic treatment option which is capable of activating intratumoral T-cells in different carcinomas. However, its therapeutic efficacy may be substantially hampered by a pre-existing dysfunctional state of T-cells, reflected by abundance of intratumoral PD-1 hi T-cells. These findings present a rationale for combinatorial approaches of TCBs with other therapeutic strategies targeting T-cell dysfunction.